Attachment, altruistic personality traits and the theory of planned behaviour as predictors of altruistic driving behaviours in young adults. (January 2023) - Dewhurst, Isabel; Rodwell, David; Lewis, Ioni
Highlights: Investigated Altruistic Driving intentions and behaviours in young drivers. Examined Theory of Planned Behaviour, Attachment, and Altruistic personality constructs. Mixed findings related to attitudes, subjective norms, and perceived behavioural control. Attachment style and altruistic personality traits not associated with altruistic driving. Altruistic driving behaviours not correlated with intentions or Perceived Behavioural Control. Abstract: Young adults are overrepresented in crash statistics compared to mature drivers. Research has addressed this concern by investigating factors related to risky driving; however, studies investigating altruistic driving are scarce. Altruistic driving, conceived as driving in a way that benefits others without expectation of benefit for oneself, may lead to less risky driving and reduction in crashes. The current study investigated psychological attachment, altruistic personality traits and Theory of Planned Behaviour (TPB) constructs as predictors of altruistic driving behaviours. The sample consisted of 17–25-year-old licensed drivers, living in Queensland, Australia, who had completed at least three quarters of mandated supervised driving practice with their mother or father as supervisor. Participants completed two linked online surveys. Survey 1 ( N  = 93) assessed sociodemographic factors, TPB variables, previous behavioural performance, attachment, altruism and intentions for altruistic driving. Survey 2, occurring two weeks later ( n  = 23), measured opportunity for and engagement in altruistic driving. The results of hierarchical multiple regression analyses supported the predictive value of the TPB constructs in explaining behavioural intention in general altruistic driving and two specific altruistic driving scenarios. However, altruism and attachment were not significant predictors of intention in any scenario. Bivariate correlations found that neither intentions or PBC (from Survey 1) were significantly associated with altruistic driving behaviours (from Survey 2) in any scenario. This research increases knowledge about motivators of altruistic driving by young drivers. This insight may be used to inform road safety interventions to motivate more altruistic driving, decrease aggression on the roads, and reduce young driver involvement in crashes.